Preheat Temperature Analysis of Cutting Knife Coating Violence in the Hard Facing Process of Aisi A35 Carbon Steel - Agus Hardjito; Imam Mashudi; Listiono Listiono; R.N. Akhsanu Takwim (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
The hard facing process is the welding process of SMAW by using a hard facing DIN 888 electrode as a hard facing to replace conventional cutting tool material. The purpose of this analysis is to determine the effect of preheating temperature on the welding of hard coatings on AISI A35 low carbon steel. The results of this study are expected to obtain optimum hardness on coated steel, from variations in the temperature of the preheating. there will be a change in the hardness of the welding deposit, the deposit will be used as cutting tools. The results of this study can be used as guidelines for making cutting tools.